Acute 40% exchange-transfusion with hemoglobin-vesicles in a mouse pneumonectomy model - Kohno, Mitsutomo; Ikeda, Tatsuhiko; Hashimoto, Ryo; Izumi, Yotaro; Watanabe, Masazumi; Horinouchi, Hirohisa; Sakai, Hiromi; Kobayashi, Koichi; Iwazaki, Masayuki (PLOS ONE, 2017)
Objectives Hemoglobin vesicles (HbVs) function as a red blood cell (RBC) substitute and are composed of purified hemoglobin encapsulated in a phospholipid bilayer membrane. The performance of HbVs as a substitute for RBC transfusions was examined in a mouse model of pneumonectomy following acute 40% exchange-transfusion with HbVs. Methods Before performing left pneumonectomies, 40% of the blood volume of mice was replaced with a) lactated Ringer’s solution (control), b) 5% recombinant human serum albumin (rHSA), c) mouse RBCs shed in rHSA (mRBCs/rHSA), or d) HbV suspended in rHSA (HbV/rHSA). We compared postoperative a) survival, b) functional recovery, and c) histopathological, immunohistochemical, and inflammatory responses among the study groups. Results In the HbV/rHSA and mRBC/rHSA groups, all mice survived ≥7 days after pneumonectomy, whereas 100% of the control mice died within a few h and 50% of mice in the rHSA group died within 24 h after pneumonectomy. Immunohistochemical staining for hypoxia-inducible factor-1α showed that hepatic and renal hypoxic injuries were prominently mitigated by HbV and mRBCs. Conclusions The oxygen-carrying performance of HbV was similar to that of mRBCs, even with impaired lung functions following pneumonectomy. HbV infusion did not interfere with the recovery from surgical injury. In the near future, HbVs could be used clinically as a substitute for the perioperative transfusion of RBCs, when or where donated RBCs are not immediately available.